Obesity and associated nutritional determinants among adolescents attending the Akwa North Secondary School in Bonamoussadi, Douala, Cameroon - Godfroy Rostant Pokam Djoko; Stephanie Rose Kenne Maffouo; Verance Carline Kegha Ngodem; Joseph Raphael Moyo Tachoum; Protais Cédric Mouenbori Sawi; Yannick Kengne Fokack; Andre Nkonjock (Public Health Frontier, 2026)
Introduction: Adolescent obesity is a major public health problem due to its global rise and its metabolic and psychosocial consequences. It results from complex interactions between nutritional, behavioural and environmental factors, particularly in urban areas where dietary shifts favour the consumption of energy-dense foods. This study aimed to determine the prevalence of obesity and to identify its nutritional determinants among adolescents at the Lycée d’Akwa North in Bonamoussadi, Douala. Methodology: A descriptive cross-sectional study with an analytical focus was conducted among 200 adolescents aged 10 to 19 years between May and October 2023. Data were collected using a structured questionnaire and standardised anthropometric measurements in accordance with WHO recommendations. Body mass index (BMI) was calculated and classified according to WHO guidelines. Statistical analyses included chi-squared tests and binary and multivariate logistic regression to identify factors associated with obesity. Results: The prevalence of obesity was 13.5%. Factors significantly associated with obesity in the multivariate analysis were frequent consumption of dairy products (>4 times per week) (AOR=3.72; p=0.002), consumption of high-fat foods (>4 times per week) (AOR=3.74; p=0.030), alcohol consumption (AOR=4.43; p=0.013) and having an obese parent (AOR=5.03; p=0.0003). These factors were all statistically significant. Conclusion: Obesity amongst adolescents at the secondary school studied is relatively high and strongly associated with unhealthy dietary behaviours as well as family history. Targeted interventions in nutrition education and the promotion of healthy lifestyles are needed in schools.